PAYROLL INFORMATION SYSTEM AT PT. ASTRO NIAGA JAYA (SIPESTRO) - Dinda Ayu Muthia; Anip Budi Setiawan; Waliyyuddin Waliyyuddin; Muhammad Syahrul Gunawan (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2019)
Abstract: Payroll is an acceptance in return from the employer to the employee for a job or service that has been done and is expressed or valued in the form of money determined on the basis of an agreement or legislation and is paid on the basis of an employment agreement between the employer and the employee including benefits, both for the employees themselves and for the family. This research takes place at PT. Astro Niaga Jaya. The payroll process at PT. Astro Niaga Jaya is still conventional. Salary calculations are based on different details that hinder the performance process of the human resources department. Errors in calculating salaries can be fatal because it will affect the preparation of financial statements. Therefore, it is necessary to have an employee payroll information system so that the human resources department is not wrong in collecting employee payroll data. The purpose of this paper is to design employee attendance and payroll information systems at PT. Astro Niaga Jaya using Waterfall method in order to produce information that is fast, precise and accurate. The Waterfall method is often used in designing an information system. Payroll Information System can work effectively and efficiently.            Keywords: payroll, information, system